Hallyu Fans’ Perceptions of The Use of Korean Swear Words in Everyday Communication - Sari, Ni Komang Cantika Hyang; Budasi, I Gede; Suardana, Made (IJLHE: International Journal of Language, Humanities, and Education, 2026)
The increasing popularity of Korean culture (Hallyu) over time has also influenced the increased exposure of Hallyu, such as Korean dramas, music, films, and language to Hallyu fans, especially fans who are non-native Korean speakers. One of the exposures of Korean language elements is swear words through media and online interactions, so that some fans also use these words, some even use them without knowing their meaning. This study aims to find out Hallyu fans’ perception of the use of Korean swear words and what factors influence them to use these words. This study is a qualitative study. Data collection was carried out by conducting semi-structured interviews using Indonesian with Hallyu fans who have different characteristics, backgrounds, and Korean proficiencies. The results of the interviews were converted into transcripts then translated into English. The collected data were analyzed using the thematic analysis method which has six stages, namely familiarization, generating codes, searching for themes, reviewing themes, defining and naming the themes, and report. The results of the study show that Hallyu fans' perceptions of Korean swear words are relative, depending on the context. The factors that influence the use of swear words are Korean content and the social environment. In addition, this study can help learners avoid misuse and develop more appropriate pragmatic competence in real-life communication.